Climate-Smart Agriculture Plan: A guide to scaling CSA - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Center for Tropical Agriculture; World Agroforestry Centre (2015)
CSA-Plan is a guide for CSA planning, programming and implementation. Sitting within each component of CSA-Plan are information, tools, and approaches to enable action. Engagement and capacity building are key crosscutting elements of CSA-Plan. CSA-Plan can be applied across levels of decision making. It allows for exchange of information between levels to maximize alignment and integration of information and planning.